Assessment of two different insulin regimens in children with type 1 diabetes: A longitudinal study - Turan, Hande; Tarcin, Gurkan; Cakir, Aydilek Dagdeviren; Kaya, Didem Gunes; Ozer, Yavuz; Ercan, Oya; Evliyaoglu, Saadet Olcay (Annals of Medical Research, 2022)
Aim: In type 1 diabetes, insulin therapy can be applied by either daily multiple dose injections with an insulin pen or subcutaneous continuous insulin infusion with an insulin pump. Numerous studies have investigated the superiority of both regimens over each other, and conflicting results have been reported. In this study, the periods when patients with type 1 diabetes were receiving subcutaneous continuous insulin infusion and multiple dose injections were compared in terms of clinical and metabolic outcomes. Materials and Methods: Children with type 1 diabetes who were receiving multiple dose injections and later switched to subcutaneous continuous insulin infusion were included. Follow-up period was evaluated in two periods: during multiple dose injections and subcutaneous continuous insulin infusion. Physical and laboratory findings, blood sugar monitoring and food chart records were compared between these two periods. Results: A total of 44 cases with a mean age of 10.6± 4.4 years were included. While a significant decrease was found in HbA1C values in the first year after the insertion of insulin pump, the values in the second year were similar to that in the pre-pump period. Mean body mass index was increased after switching to subcutaneous continuous insulin infusion. In the second year of the subcutaneous continuous insulin infusion, a significant decrease in hypoglycemic events was observed. Conclusion: In terms of glycemic control, no difference was found between subcutaneous continuous insulin infusion and multiple dose injections in the long term suggesting that similar clinical results can be obtained with multiple dose injections therapy in cases who cannot afford an insulin pump. Considering that HbA1c levels tend to increase in the second year of subcutaneous continuous insulin infusion and similarly body mass index after switching to subcutaneous continuous insulin infusion, clinicians should be aware of the misuse of insulin pump, and patients’ education should be revised regularly.